An Isolable Diboron‐Centered Diradical with a Triplet Ground State. Issue 28 (24th April 2017) - Wang, Lei; Fang, Yong; Mao, Haochuan; Qu, Yi; Zuo, Jiacheng; Zhang, Zaichao; Tan, Gengwen; Wang, Xinping
Abstract: Two new diboranes, 2, 6‐bis(BMes2 )mesitylene (1 ) and 3, 3′‐bis(BMes2 )bimesitylene (3 ), were synthesized. Two‐electron reduction of1 with elemental potassium afforded the C−H activation product [(18‐c‐6)K(THF)2 ]2 + ⋅2 2− bearing a BC3 four‐membered ring as colorless crystals, whereas the reduction of3 with potassium led to the isolation of [(18‐c‐6)K(THF)2 ]2 + ⋅3 2−.. as dark blue crystals. Both reduction products were characterized by structural and spectroscopic methods. Electron paramagnetic resonance (EPR) spectroscopy and theoretical calculations revealed that the electron spin density of3 2−.. mainly resides on the two boron nuclei and features a triplet ground state, which was confirmed by superconducting quantum interference device (SQUID) measurements as well as theoretical calculations.3 2−.. represents the first structurally characterized boron‐centered diradical with a triplet ground state. In addition, the reactivity of [(18‐c‐6)K(THF)2 ]2 + ⋅3 2−.. toward PhSeSePh and n Bu3 SnH was investigated, which is consistent with its radical character. Abstract : Stable Diradical : A diboron diradical featuring a triplet ground state is isolated and fully characterized by single‐crystal X‐Ray diffraction, electron paramagnetic resonance spectroscopy, and UV/Vis spectroscopy, as well as superconducting quantum interference device (SQUID) measurements, in conjunction with DFT calculations. In addition, its reactivity is investigated.